Are urban poverty and undernutrition growing?: newly assembled evidence - Haddad, Lawrence James; Ruel, Marie T.; Garrett, James L. (International Food Policy Research Institute, 1999)
The population of the developing world is becoming more urban. Are poverty and undernutrition beginning to relocate to urban areas as well? We use survey data on poverty (from 8 countries) and on child undernutrition (from 14 countries) to address this question. Using data from the past 15-20 years, we find that in a majority of countries the absolute number of poor and undernourished individuals living in urban areas has increased, as has the share of poverty and undernourishment coming from urban areas. Given these trends and the current stock of knowledge as to the levels, determinants, and solutions to urban poverty and undernutrition, we argue for more research on these issues.